2012
DOI: 10.1038/jhh.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology and pregnancy-related hypertensive complications: a systematic review

Abstract: Hypertensive complications in pregnancy are the leading cause of maternal morbidity, at least in the developed countries. In recent years, infertility issues are managed with ever growing therapeutic options namely assisted reproductive technologies (ART), which improve the ratio of successful induction of pregnancy. It is still debated whether various ART modalities are associated with adverse pregnancy outcomes, including hypertensive complications, particularly with higher incidence of preeclampsia. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 85 publications
6
103
2
4
Order By: Relevance
“…Perinatal outcome (Table 5) including mean birth weight, APGAR score, incidence of SFD, hyperbilirubinemia and respiratory distress was significantly higher in donor oocyte group as compared to spontaneous conception group (p=0.001) but outcomes including mean birth weight, APGAR score, respiratory distress, congenital anomaly did not suggest any significant variation between the donor and self-oocyte IVF cycles (P>0.05). 17 Thomopoulos showed that ART pregnancies, especially IVF techniques, are accompanied by increased risks for gestational hypertension as compared with non-ART pregnancies, even after adjustment for confounding factors. 17 The success of pregnancy depends upon an appropriate implantation and placental function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal outcome (Table 5) including mean birth weight, APGAR score, incidence of SFD, hyperbilirubinemia and respiratory distress was significantly higher in donor oocyte group as compared to spontaneous conception group (p=0.001) but outcomes including mean birth weight, APGAR score, respiratory distress, congenital anomaly did not suggest any significant variation between the donor and self-oocyte IVF cycles (P>0.05). 17 Thomopoulos showed that ART pregnancies, especially IVF techniques, are accompanied by increased risks for gestational hypertension as compared with non-ART pregnancies, even after adjustment for confounding factors. 17 The success of pregnancy depends upon an appropriate implantation and placental function.…”
Section: Resultsmentioning
confidence: 99%
“…17 Thomopoulos showed that ART pregnancies, especially IVF techniques, are accompanied by increased risks for gestational hypertension as compared with non-ART pregnancies, even after adjustment for confounding factors. 17 The success of pregnancy depends upon an appropriate implantation and placental function. 18 The risk of hypertensive disorders of pregnancy in DO pregnancies can be explained on the basis of an immunological mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple pregnancies are frequent in ART usage: the incidence of twins in in vitro fertilisation (IVF)-conceived pregnancies is approximately 27%. 3 The extent to which women are able to cope with the haemodynamic challenges imposed by pregnancy, particularly multiple pregnancies, depends on the nature, severity and current status of the underlying heart condition. 7 Despite the broad morphological and functional diversity of heart disease, only a few parameters have been shown to be associated with complications in pregnancy: previous cardiac events (heart failure, transient ischaemic attack or stroke before pregnancy) or arrhythmia; poor functional New York Heart Association (NYHA) class (>II) or cyanosis; LV systolic dysfunction (ejection fraction <30%); left heart obstruction; and pulmonary arterial hypertension.…”
Section: Risk Stratification and Counsellingmentioning
confidence: 99%
“…3 Although data are inconsistent, FTs have been linked to PIH. 1,3,29,30 In their systematic review, Thomopoulos et al analysed 47 studies and found that ARTs, and IVF in particular, are associated with an increased risk of gestational hypertension and pre-eclampsia. 3 Multiple pregnancies and advanced maternal age further increase the risk of hypertensive complications.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation